Masalah Sosial dalam Cerpen “Guru” Karya Putu Wijaya - Rochmansyah, Bagaskara Nur; Firdaus, Winci; Leonita, Leonita (Salingka, 2024)
This research aims to describe the social problems in the short story "Guru" by Putu Wijaya. This research uses a literary sociology approach according to Wellek and Warren with a focus on the sociology of literary works. The data collection technique used is the first reading technique (heuristics) and the second reading technique (hermeneutics) as a data analysis technique. The results of this research show four classifications of social problems. The poverty depicted is the condition of teachers who are closely related to poverty, lacking everything, and living a miserable life. Family conflict includes conflicting ideals about being a teacher. The problem of the idealism of the young generation in contemporary society is shown in the form of the firmness of their idealism in their dreams of becoming teachers even though they are constantly being persuaded, rewarded, scolded, and even threatened with death by their parents. The problem with contemporary society's mindset that is shown is the parents' view of the teaching profession which is not desired by society and is closely linked to poverty, adversity and death. Teaching is seen as an unpromising profession and people who become teachers are pessimistic.AbstrakPenelitian ini bertujuan untuk mendeskripsikan masalah sosial yang terdapat di dalam cerpen “Guru” karya Putu Wijaya. Penelitian ini menggunakan pendekatan sosiologi sastra menurut Wellek dan Warren dengan fokus sosiologi karya sastra. Teknik pengumpulan data yang digunakan adalah teknik pembacaan pertama (heuristik) dan teknik pembacaan kedua (hermeneutik) sebagai teknik analisis data. Hasil penelitian ini menunjukkan empat klasifikasi masalah sosial. Kemiskinan yang tergambar adalah kondisi guru yang erat dengan kemiskinan, serba kekurangan, dan hidup sengsara. Konflik keluarga meliputi pertentangan idealisme menjadi guru. Masalah idealisme generasi muda dalam masyarakat kontemporer yang ditampakkan berupa teguhnya idealisme cita-cita menjadi guru walau terus dibujuk, akan dihadiahi, dimarahi, bahkan diancam akan dibunuh oleh orang tuanya. Masalah pola pikir masyarakat kontemporer yang ditampakkan adalah pandangan orang tua terhadap profesi guru yang tidak didambakan oleh masyarakat dan erat dengan kemiskinan, keterpurukan, serta kesengsaraan. Guru dipandang menjadi profesi yang tidak menjanjikan dan orang yang menjadi guru adalah orang yang pesimis.